Aneurisma del seno de Valsalva con doble rotura a la arteria pulmonar y al ventrículo derecho. Reporte de un caso y revisión de la literatura. - Custodio, Jesús; Arauco, Víctor; Ramirez, Milvio; Cerron, Carlos (Revista Médica Herediana, 2013)
We report a case of a 21 year old female who presented with congestive cardiac failure. In initial investigations an aneurysm of sinus of Valsalva was found ruptured to the pulmonary artery. It was surgically repaired uneventfully. The patient was discharged home after 10 days. During the follow-up appointments she was found to have reappearing symptoms of congestive cardiac failure. This lead to her readmission and a repeated cardiac catheterization found her to have an aneurysm of sinus of Valsalva reuptured to the right ventricule, which in a second operation was succesfully repaired. We review the bibliography over the last 20 year finding the unusual presentation of the rupture to the pulmonary artery. We point out the importance of a sharp clinical examination and the preference of cardiac catheterization to make the diagnosis.